2020
DOI: 10.3390/ijerph17228594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes and Its Association with Added Sugar Intake in Citizens and Refugees Aged 40 or Older in the Gaza Strip, Palestine

Abstract: Background: Little is known about the prevalence and risk factors of diabetes among Gaza Palestinians, 64% of whom are refugees with exceeded sugar intake. We aimed to estimate the prevalence of type 2 diabetes (T2D) and its association with added sugar intake among residents, with regular visits to primary healthcare centers (PHCs) across Gaza. Methods: From October to December of 2019, a cross-sectional survey was conducted among 1000 citizens and refugees in nine PHCs selected from the five governorates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Many prospective and retrospective studies have been conducted with varying and inconsistent results [ 119 , 120 ]. However, the majority of research conducted has found a positive association between sugars [ 121 ], particularly fructose and SSB consumption [ 35 , 119 , 122 ], and risk for diabetes type 2 (T2DM) (see Table 2 ). Several animal and human studies have observed impaired insulin signalling and increased fasting glucose and insulin resulting from SSB consumption [ 61 , 123 , 124 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many prospective and retrospective studies have been conducted with varying and inconsistent results [ 119 , 120 ]. However, the majority of research conducted has found a positive association between sugars [ 121 ], particularly fructose and SSB consumption [ 35 , 119 , 122 ], and risk for diabetes type 2 (T2DM) (see Table 2 ). Several animal and human studies have observed impaired insulin signalling and increased fasting glucose and insulin resulting from SSB consumption [ 61 , 123 , 124 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to a flaw in the social support system for diabetes in the Gaza Strip, adherence to non-pharmacological intervention in diabetes control was suboptimal [33]. The percentage of undiagnosed adult DM was 16.8% of the 1,000 subjects included in the cross-sectional study, which is strongly associated with sugar intake [11]. DM can be controlled with the help of social support.…”
Section: Palestinian Populationmentioning
confidence: 99%
“…Another systematic review and meta-analysis reported that about 46 million individuals now have diabetes in the Middle East, with a prevalence of 14.6% that varied among countries from 2.6% to 21.9% [8]. Although the prevalence of diabetes mellitus among refugees and internally displaced persons was not precisely estimated in each of these nations, it was found in samples of refugees who were transferred to other nations [9][10][11][12]. Due to the multifaceted crisis that the Ministry of Health in these countries is facing, there are numerous criticisms of the prevalence of diabetes in these countries, including the updated population census and the accuracy of health services in registering and monitoring diabetes patients.…”
Section: Introductionmentioning
confidence: 99%
“…Public health nutrition-related problems in OPT highlight the need for qualified nutritionists, dietitians, and educational institutes to implement intervention plans, develop policies that help in health promotion and disease prevention to address existing and future anticipated public health nutrition problems in OPT, and improve nutritional health outcomes. The Middle East has been identified as a region with a considerable need for trained nutritionists and dietitians in order to address the escalating double burden of nutrition-related diseases, particularly for internally displaced individuals, refugees, and the vulnerable population of OPT (Damiri et al, 2018; Ghattas et al, 2020; Hwalla et al, 2016; Jebril et al, 2020; Kitamura et al, 2018; Rahim et al, 2014; Salti & Ghattas, 2016).…”
Section: Introductionmentioning
confidence: 99%